Potential roles of gut microbiota and microbial metabolites in chronic inflammatory pain and the mechanisms of therapy drugs. (July 2022) - Li, Jia-Shang; Su, Shu-Lan; Xu, Zhuo; Zhao, Li-Hui; Fan, Ruo-Ying; Guo, Jian-Ming; Qian, Da-Wei; Duan, Jin-Ao
Observational findings achieved that gut microbes mediate human metabolic health and disease risk. The types of intestinal microorganisms depend on the intake of food and drugs and are also related to their metabolic level and genetic factors. Recent studies have shown that chronic inflammatory pain is closely related to intestinal microbial homeostasis. Compared with the normal intestinal flora, the composition of intestinal flora in patients with chronic inflammatory pain had significant changes in Actinomycetes, Firmicutes, Bacteroidetes, etc. At the same time, short-chain fatty acids and amino acids, the metabolites of intestinal microorganisms, can regulate neural signal molecules and signaling pathways, thus affecting the development trend of chronic inflammatory pain. Glucocorticoids and non-steroidal anti-inflammatory drugs in the treatment of chronic inflammatory pain, the main mechanism is to affect the secretion of inflammatory factors and the abundance of intestinal bacteria. This article reviews the relationship between intestinal microorganisms and their metabolites on chronic inflammatory pain and the possible mechanism.